Adapting anatomy teaching to surgical trends: a combination of classical dissection, medical imaging, and 3D-printing technologies. - Fasel, Jean; Aguiar, Diego; Kiss-Bodolay, Daniel; Montet, Xavier; Kalangos, Afksendiyos; Stimec, Bojan; Ratib, Osman (Surgical & Radiologic Anatomy, 2016)
Purpose: Many regions worldwide report difficulties in recruiting applicants to surgery. One strategy proposed to reverse this trend consists of early exposure of medical students to the field. Against this backdrop, the present study presents an innovative approach for anatomy teaching, integrating a surgically relevant trend: 3D printing. Methods: Whole-body computed tomography (CT) was made of two cadavers. Twelve students performed measurements and 3D reconstructions of selected anatomical structures (Osirix, Mimics). 3D printed (3DP) models were obtained (ZPrinter 310 Plus), and the students completed the analogous measurements on these replicas. Finally, classical anatomical dissection was performed and the same parameters were measured. The differences between the values obtained by the three modalities were submitted to standard statistical analysis (Wilcoxon two-tail paired test). Results: Qualitative comparison of the digital 3D reconstructions based on the students' manual CT segmentation and the anatomical reality showed excellent correlation. Quantitatively, the values measured on the CT images and the physical models created by 3D printing differed from those measured on the cadavers by less than 2 mm. Students were highly appreciative of the approach (CT, 3DP, cadaver). Their average satisfaction score was 5.8 on a 1-6 scale. Conclusions: This study shows that the approach proposed can be achieved. The results obtained also show that CT-based 3D printed models are close to the authentic anatomic reality. The program allows early and interactive exposure of medical students to a surgically relevant trend-in this case 3D printing.